2014
DOI: 10.1515/forj-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Daily activity rhythm and habitat use of the semi-free European bison herd during the growing season / Denní aktivita a využití prostředí zubrem evropským (Bison bonasus) během vegetační sezóny

Abstract: The European bison (Bison bonasus) became extinct in the wild in the 20th century. Due to successful reintroductions of captive individuals, the free-ranging bison population has been steadily increasing. However, the population consists of small and isolated herds whose survival depends on creating larger and connected populations. Detailed knowledge of movement and habitat use in human-dominated landscape is essential for further successful reintroductions of the European bison. Therefore, we studied daily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…The studies of the European bison show the complex importance of both habitats, open and forests [21,26,27]. In Židlov (Czech Republic) as well as in our study, the bison herd preferred forested habitats [18] during the daytime and more open lands at night. This finding supports an assumption that the European bison tends to be a forest specialist in Central Europe [28].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The studies of the European bison show the complex importance of both habitats, open and forests [21,26,27]. In Židlov (Czech Republic) as well as in our study, the bison herd preferred forested habitats [18] during the daytime and more open lands at night. This finding supports an assumption that the European bison tends to be a forest specialist in Central Europe [28].…”
Section: Discussionsupporting
confidence: 75%
“…Other studies have indicated that European bison prefer open habitats [1,9,26,29]. The night and daytime differences in the selection of forest or agricultural land support the hypothesis that bison habitats are determined by disturbance (human and predators) avoidance rather than habitat preference [18]. Studies have shown the importance of landscape and habitat for large ungulate species [10,30].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Wołoszyn-Gałęza et al 11 found that, in winter periods, European bison preferred deciduous and mixed forest areas located at lower altitudes above sea level; however, in the growing season these animals were much more likely to stay in coniferous forest areas with a low canopy cover. Other studies have indicated that European bison have a preference for coniferous stands 12 , 13 . Kuemmerle et al 14 showed that each European bison population’s preferences for particular types of habitats differed significantly.…”
Section: Introductionmentioning
confidence: 95%